(untitled) (Eurasian Medical Research Periodical, 2022)
One of the problems that worries modern people today is non-communicable diseases caused by inactivity and malnutrition. In this study, an attempt was made to find a simple solution to this problem. It is said that various legumes and legumes can be used to slowly eradicate non-communicable diseases.